2014
DOI: 10.2215/cjn.10941013
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fibroblast Growth Factor 23 Testing in Patients with Kidney Disease

Abstract: The emergence of fibroblast growth factor 23 as a potentially modifiable risk factor in CKD has led to growing interest in its measurement as a tool to assess patient risk and target therapy. This review discusses the analytical and clinical challenges faced in translating fibroblast growth factor 23 testing into routine practice. As for other bone mineral markers, agreement between commercial fibroblast growth factor 23 assays is poor, mainly because of differences in calibration, but also, these differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 175 publications
3
42
1
1
Order By: Relevance
“…FGF23 Cterminal enzyme-linked immunosorbent assay (ELISA) yields the sum of the C-terminal fragment and intact FGF23 [74,75] , whereas FGF23 intact ELISA simply yields iFGF23, which constitutes the biological activity of FGF23 and is involved in pathophysiological processes in subjects with CKD and other phosphatemic disorders [74,76,77] . Animal studies have shown that an increase in cFGF23 by C-terminal ELISA may be due to the increase in C-terminal fragments acting as an acute-phase reactant under stressful conditions because iFGF23 was not elevated [78] .…”
Section: High Fgf23 In Ckdmentioning
confidence: 99%
“…FGF23 Cterminal enzyme-linked immunosorbent assay (ELISA) yields the sum of the C-terminal fragment and intact FGF23 [74,75] , whereas FGF23 intact ELISA simply yields iFGF23, which constitutes the biological activity of FGF23 and is involved in pathophysiological processes in subjects with CKD and other phosphatemic disorders [74,76,77] . Animal studies have shown that an increase in cFGF23 by C-terminal ELISA may be due to the increase in C-terminal fragments acting as an acute-phase reactant under stressful conditions because iFGF23 was not elevated [78] .…”
Section: High Fgf23 In Ckdmentioning
confidence: 99%
“…4 FGF23 is a valuable biomarker in CKD. 5 FGF23 is a member of the FGF family which promotes negative external phosphate balance through inhibition of intestinal absorption and enhanced renal excretion. 6 Klotho protein is beta-glucuronidase which is associated with longevity, 9 cardiovascular disease, 12 and calcium/ phosphorous homeostasis in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main explanations for the high rate of mortality due to cardiac disease is various conditions such as heart calcification, diastolic dysfunction, and sudden cardiac death in patients with hypertrophy of left ventricle. The risk of sudden heart death rises with progressive loss of renal function before dialysis (3,4). Around 25% of individuals on dialysis die of sudden heart death as a one hundred increased fold risk compared to the general population.…”
mentioning
confidence: 99%
“…Generally, in chronic renal failure, other major risk factors for hypertrophy of left ventricle are volume overload, anemia and hypertension. However, aggressive correction of these abnormalities leads to regression of hypertrophy of left ventricle in below than 50% of individuals on dialysis, implying the presence of some other parameters specific to chronic renal failure that are responsible for high heart and vessels disease in these group (2)(3)(4)(5). Furthermore, it is well documented that individuals with heart and vessel disease have a high risk of kidney disturbance.…”
mentioning
confidence: 99%
See 1 more Smart Citation